Impact of Customer Relationship Management on Customer Retention: A Study in the Private Healthcare Sector in Jaffna, Sri Lanka - Karunanithy, M. (University of Vavuniya, 2022)
Customer retention is crucial to organizations for their sustainability. Retaining customers is cost beneficial rather than acquiring new. Building a mutually beneficial relationship with customers is becoming important in today’s contemporary context. Organizations are trying to adopt Customer Relationship Management (CRM) to gain competitive advantages in day-to-day market especially for the sustainability of the business. CRM, as a strategy can improve the image of the organization and increasing purchasing intention of customers which gives room for customer retention. In this research, the researcher intends to study the impact of CRM on Customer Retention (CR) by focusing to the private healthcare sector in Jaffna District with the objectives to find out the followings: factors influencing the CRM in private sector healthcare organizations, the significant association between sub dimensions of the service quality and the significant differences in CRM practices adopted by private sector healthcare organizations. A list of registered private hospitals operating in Jaffna obtained from the Regional Director of Health Services in Jaffna and hospitals which are giving importance to CRM were considered for data collection. A questionnaire was developed for customers. It was intended to collect data from 500 patients as from the selected hospitals in Jaffna. Only 359 fully completed questionnaires were considered for analysis. The data were analyzed by using advanced multivariate analysis as Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA) and Structural Equation Modeling. These techniques were utilized to test measurement model and the research hypotheses. EFA was done through SPSS to identify the variable(s) as most contributors. Out of five well known SERVQUAL variables, only three were influenced highly. Besides, CFA was done through AMOS to find out the association of constructs comprising the measurement model, and the results showed that CRM had a significant and positive impact on customer retention.
Keywords: Healthcare Organization; Customer Relationship Management; Customer Retention; Customer Loyalty; SERVQUAL